2022
DOI: 10.3389/fpsyg.2022.961798
|View full text |Cite
|
Sign up to set email alerts
|

Effect of decrease of physical activity on depression and anxiety after the COVID-19 lockdown: A survey study

Abstract: PurposeWe focused on changes in the amount of physical activity (PA) and depression and anxiety symptoms in people, who were previously regularly physically active, as they were all members of fitness centers at time of lockdown because of COVID-19.Materials and methodsWe sampled 150 fitness center members, tested individually in facilities of fitness centers. Depression and anxiety were measured with subscales of Personality Assessment Inventory (PAI) and PA was measured with global physical activity question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 66 publications
0
5
1
1
Order By: Relevance
“…Spending a lot of time on social media can prevent people from exercising, which results in lower levels of physical activity. 33 As reported by 52.1% of the study’s participants, using Instagram ® excessively while studying dentistry might be harmful to the students’ mental and emotional health. Increased levels of worry, despair, tension, and even the possibility of addiction is included in this.…”
Section: Discussionmentioning
confidence: 90%
“…Spending a lot of time on social media can prevent people from exercising, which results in lower levels of physical activity. 33 As reported by 52.1% of the study’s participants, using Instagram ® excessively while studying dentistry might be harmful to the students’ mental and emotional health. Increased levels of worry, despair, tension, and even the possibility of addiction is included in this.…”
Section: Discussionmentioning
confidence: 90%
“…According to cross‐sectional research, there is a strong link between increased regular physical activity and lower levels of anxiety as well as depression in older adults and adolescents. Kajtna sampled fitness centers using surveys and depression as measured by the Personality Assessment Inventory (PAI) and Global Physical Activity Questionnaire (GPAQ) and found a significant association between movement and decreased depression 30 . Additionally, Taylor performed a review on socioeconomic status and mental health and found increased vigorous exercise was linked to less emotional distress, even after controlling for social class and health status 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Kajtna sampled fitness centers using surveys and depression as measured by the Personality Assessment Inventory (PAI) and Global Physical Activity Questionnaire (GPAQ) and found a significant association between movement and decreased depression. 30 Additionally, Taylor performed a review on socioeconomic status and mental health and found increased vigorous exercise was linked to less emotional distress, even after controlling for social class and health status. 31 Exercise was linked to lower rates of depression among undergraduate university students, even after age and sex were taken into account.…”
Section: Discussionmentioning
confidence: 99%
“…Physical inactivity remains a significant problem that negatively impacts the physical ( Haskell et al, 2007 ) and mental health of adults ( Spalter et al, 2015 ; Kajtna and Vučković, 2022 ). One of the fastest growing sectors in physical activity and exercise is the fitness industry ( Rodriguez, 2019 ; Yi et al, 2021 ), which is particularly popular among young people ( Ong et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%